Effect of vacuum infusion of pectinase and calcium on the texture and colour of minimally processed guava (psidium guajava l.) - Osman, Azizah; S., Muhamad Surairi; Liu, F.; Mohd Ghazali, Hasanah; Abdul Rahman, Russly (2001)
Guava (psidium guajava L.) ofcommercial maturity that was minimally processed were dipped in pectinase solutions at concentrations of 0, 0.5, 1.0 and 1.5% (volume/volume) under reduced pressure of76, 55, 35 and 20 cm Hg. The treated fruit wedges were then dipped in calcium lactate solution at concentrations of0, 0.5, 1.0, 1.5 and 2.0% (w/v). All samples were then stored for 7 days at 7+l°C; 75-92% RH. Fruits that were not treated with pectinase and calcium lactate served as control. This experiment was aimed at determining the effect of using pectinases, calcium lactate and reduced pressure on retaining the texture and colour of minimally processed guava during storage. Fruits dipped in pectinase and under reduced pressure retained the firmness of the fruit wedges. It was observed that infusion with 1% pectinase gave a positive effect on physical changes. Reduced pressure of35 cm Hg was also found to be the optimum pressure. However, overall results obtained reveal that combination treatment of enzyme infusion at reduced pressure followed by calcium dipping caused the fruits to loose its firmness and colour during storage.